Psychosocial correlates of depression and anxiety among treatment-seeking individuals with opioid dependence: a cross-sectional study - Sarkar, Siddharth; Pandit, Muzafar; Negi, Parvender Singh; Mathur, Rahul; Balhara, Yatan Pal Singh (Frontiers in Psychiatry, 2025)
Background and aimsOpioid dependence is commonly comorbid with depression and anxiety, which contribute to greater disability and poorer quality of life. This study assessed the prevalence of these comorbidities and their socio-demographic and clinical correlates in treatment-seeking individuals with opioid dependence in India.MethodologyWe conducted a cross-sectional study at a tertiary care center in North India. A total of 255 adult patients diagnosed with opioid dependence (ICD-11) were recruited after fulfilling inclusion and exclusion criteria. Depression and anxiety were assessed using the Patient Health Questionnaire-9 (PHQ-9) and the Generalized Anxiety Disorder-7 (GAD-7). Quality of life and disability were measured using the WHOQOL-BREF and WHODAS 2.0. Logistic regression was performed to examine predictors of moderate-to-severe depression (PHQ-9 ≥10) and anxiety (GAD-7 ≥10). Ethical approval was obtained from the Institutional Ethics Committee.ResultsThe participants had a median age of 28 (24-32) years; heroin was the predominant opioid (87%), and 30% reported injecting use. More than half (57%) had moderate-to-severe depression and 42% had moderate-to-severe anxiety, which were strongly correlated (r = 0.90). Both conditions were associated with higher disability and poorer quality of life across all domains. In univariate analyses, unemployment, stigma, interpersonal problems, and lack of abstinence were consistently linked with worse outcomes. Multivariable models showed that depression was independently predicted by stigma (OR = 2.95), interpersonal problems (OR = 4.21), and absence of opioid agonist treatment (OR = 0.30, protective). For anxiety, interpersonal problems were the strongest predictor (OR = 4.98), while past-month abstinence was protective (OR = 0.45).ConclusionOur findings highlight the significant burden of depression and anxiety among individuals with opioid dependence, with significant implications for disability and quality of life. Future research should focus on stigma reduction, optimization of opioid agonist treatment, and integration of mental health care within addiction services.